Core Functional Requirements for Fiscal Management Systems - Hashim, Ali.; Allan, Bill. (Washington, D.C. : International Monetary Fund, 1994)
This paper presents a framework for planning the development of computerized government budgeting and accounting systems in economies in transition and developing economies. It argues that a comprehensive framework is needed to enable fiscal management issues to be addressed effectively, then outlines a methodology for planning systems development and proposes strategies for implementing the methodology in transitional and developing economies.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet